2011
DOI: 10.1002/jor.21425
|View full text |Cite
|
Sign up to set email alerts
|

Gas7 mediates the differentiation of human bone marrow‐derived mesenchymal stem cells into functional osteoblasts by enhancing Runx2‐dependent gene expression

Abstract: The differentiation of bone marrow mesenchymal stem cells (MSCs) into osteoblasts is a crucial step during bone formation. However, the mechanisms regulating the early stages of osteogenic differentiation are not fully understood. In the present study, we found that growth-arrest specific gene 7b (Gas7b) was up-regulated during dexamethasone-induced differentiation of human MSCs (hMSCs) into osteoblasts. Knockdown of Gas7 using short-hairpin RNA decreased the expression of the osteogenic transcription factor R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Among these targets are the receptor for Wnt proteins frizzled-class-receptor-3 (FZD3), involved in MSCs differentiation into hepatocytes 55 and the zinc-finger-protein-91 (ZFP91), which affect engraftment of hematopoietic stem cells 56 . Similarly, growth-arrest specific gene-7 (Gas7) and S/G2 cyclin, cyclin G2 (CCNG2), targets of mir378, regulate stem cell differentiation 57, 58 . Other targets of miR378 include genes related mainly to mitochondria, transcription, cytoskeleton, calcium signaling, apoptosis, and proteolysis, underscoring the versatility of EV-miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Among these targets are the receptor for Wnt proteins frizzled-class-receptor-3 (FZD3), involved in MSCs differentiation into hepatocytes 55 and the zinc-finger-protein-91 (ZFP91), which affect engraftment of hematopoietic stem cells 56 . Similarly, growth-arrest specific gene-7 (Gas7) and S/G2 cyclin, cyclin G2 (CCNG2), targets of mir378, regulate stem cell differentiation 57, 58 . Other targets of miR378 include genes related mainly to mitochondria, transcription, cytoskeleton, calcium signaling, apoptosis, and proteolysis, underscoring the versatility of EV-miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we also found a functional link between the expression of Gas7 and the processes of chondrogenesis and osteogenesis in human bone marrow-derived human MSCs [12, 13]. …”
Section: Gas7: a Pombe Cdc15 Homology Proteinmentioning
confidence: 86%
“…Recently, we observed that Gas7 represents a novel regulator of MSC-based osteogenesis [13]. Gas7 controls the differentiation of human MSCs into functional osteoblasts by enhancing Runx2-dependent gene expression.…”
Section: Gas7 In Msc-based Osteogenesismentioning
confidence: 99%
“…In particular, Gas7 induces neurite outgrowth. Report by Hung et al (2011) shows that Gas7 regulates mesenchymal stem cell differentiation. This implies that Gas7 has a role in cell differentiation process.…”
Section: )mentioning
confidence: 99%